EFFECT OF ORGANIZATIONAL CULTURE AND TRAINING EFFECTIVENESS TO EMPLOYEE PERFORMANCE WITH WORK MOTIVATION AS INTERVENING VARIABLE - Dibyantoro; Prahiawan, Wawan; Ramdansyah, Agus David (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The purpose of the study was to examine work motivation as an intervening organizational culture and the effectiveness of training on employee performance. Survey method and simple random sampling technique were used for data collection with the help of a questionnaire based on a 10-point Likert scale. The number of samples of 100 employees is used to test the hypothesis. The research model used is Structural Equation Modeling (SEM) with the help of SmartPLS 3.2.9 to perform data processing. The results showed that organizational culture and training effectiveness had a positive and significant influence on work motivation. Organizational culture has a positive and insignificant effect on employee performance. Meanwhile, the effectiveness of training and work motivation has a positive and significant effect on employee performance